FREQUENCY OF PLACENTA PREVIA IN WOMEN WITH HISTORY OF PREVIOUS CAESAREAN AND NORMAL VAGINAL DELIVERIES - Bashir, Adeela; Jadoon, Humaira Naz; Abbasi, Aziz -un-Nisa (Journal of Ayub Medical College Abbottabad, 2012)
Background: Placenta previa is known to be associated with previous caesarean deliveries, advanced maternal age, increasing parity, smoking, curettage and myomectomy. This study was carried out to compare the frequency of placenta previa, in women with previous caesareans versus those with normal vaginal deliveries. Methods: It was one year study conducted at the Department of Obstetrics and Gynaecology Unit B, Ayub Teaching Hospital, Abbottabad. One hundred women were included in the study, 50 in Group A with previous caesarean deliveries, and 50 in Group B with previous normal vaginal deliveries. Frequency of placenta previa in both groups was analysed. Results: Placenta previa was found in one (2%) woman in Group A, and in two women (4%) in Group B. It was not found in para 4 or less in both groups. One woman in Group A and two women in Group B with parity 4 or more had placenta previa (p<0.05). None of the women with previous one scar had placenta previa, while with previous 2 scars one had placenta previa (p<0.05). One woman with placenta previa in Group A and both women with placenta previa in Group B were more than 25 years old. Placenta previa was not found in women below 25 years of age. Conclusion: Previous one caesarean section did not increase the frequency of placenta previa. Increasing number of scars, increasing maternal age beyond 25 years and increasing parity beyond 4 were associated with placenta previa. Keywords: Placenta, placenta previa, caesarean section, scar, vaginal delivery, parity